Estimates of vertical tectonic stress in the northwest Ethiopian plateau using topography and gravity data - Muluken Kassa (Heliyon)
The northwest Ethiopian plateau is one of the globe's most complex tectonic zones. Within the area, the previous geological and geophysical investigations revealed volcanism and deformation effects but did not thoroughly examine crust movement, isostatic compensation, and deformation patterns. The main focus of this study is to use high-resolution topography and gravity data to map the region's vertical tectonic stress and crustal thickness, including isostatic and gravity Moho, in order to obtain a better understanding of the tectonics of the area. Here, the Airy model is utilized to estimate the isostatic Moho, which is dependent on topography data. The regional Bouguer anomaly map is estimated using the Butterworth filter, and the resulting map is then inverted using 3D Parker-Oldenburg inversion technique to generate a gravity Moho for the area. Estimated results from power density spectrum analysis and previously published seismic data constrain the inversion outcome. The isostatic and gravity Moho estimations vary between 32.6 and 54.4 km and between 30 and 56.9 km, respectively. The Moho depth results agree with previous seismic and global crustal thickness models. Vertical tectonic stress is generated beneath the region based on isostatic and gravity Moho estimates. The results confirm that both the Blue Nile and Tana escarpments have positive vertical tectonic stress, indicating that the crust beneath isostatically readjusted. The Lake Tana and areas adjacent to the Lake Tana, including the Debre Tabor Graben, Guna, Choke, and Guguftu mountains, are characterized by negative vertical tectonic stress. This negative vertical tectonic stress agrees very well with regional geomorphic and tectonic elements of the region. The study offers in-depth understanding of the area tectonics.